Diagnostik bei Polyneuropathien - Heuss, D. (Internist, 2020)
The diagnosis of polyneuropathy (PNP) is based on the anamnesis and description of complaints of the patient and clinical findings. The type of distribution as well as known diseases and drug toxic factors can provide indications. Electromyography and electroneurography can be used to differentiate between axonal and demyelinating PNP. The laboratory examinations are initially directed towards frequent and treatable causes. These are then expanded depending on the suspected diagnosis. Analysis of cerebrospinal fluid (CSF) is facultative and should be carried out when there is a suspicion of a certain form of PNP with CSF findings indicative of the diagnosis. Nerve biopsy is indicated when the etiology of a severe or progressive PNP cannot be clarified by less invasive means and can have consequences for the treatment. A genetic investigation can be meaningful with a positive family anamnesis or with typical signs of hereditary PNP. Depending on the neuropathy and context, the diagnostic approach is structured differently. The special diagnostics for small fiber neuropathy and amyloid neuropathy as well as for diabetes and alcohol abuse are dealt with in detail in this article. Numerous cases of polyneuropathy remain unexplained and regularly have a favourable prognosis.
CRIS-Team Scopus Importer:2020-03-13
Keywords: Alcohol abuse; Amyloid neuropathies; Diabetes mellitus; Diagnostic certainty; Small fiber neuropathy